Pengaruh Customer Experience dan Customer Engagement Terhadap Customer Satisfaction Pada Nasabah Milenial Bank Syariah Indonesia Di Kota Kendari - Munadi Idris (Program Studi Ekonomi Syariah IAIN Parepare, 2026)
This research is motivated by the critical role of service quality in the Islamic banking industry, particularly how customer experience and customer engagement can affect customer satisfaction. The purpose of this research is to analyze the partial and simultaneous influence of customer experience and customer engagement on customer satisfaction among customers of Bank Syariah Indonesia (BSI) in Kendari. This type of research uses a quantitative approach with an explanatory survey method. Data was collected through a questionnaire distributed to 100 respondents using a purposive sampling technique, and then analyzed using multiple linear regression with the help of SPSS v 27 statistical software. The conclusion of this study is that both customer experience and customer engagement have a positive and significant influence on customer satisfaction, where customer experience is found to be the dominant factor. These findings imply that the bank needs to prioritize the creation of positive sensory and emotional service experiences while building interactive connections to enhance and maintain sustainable customer satisfaction.